Hearing Loss in Low Birth Weight Neonates: A Comparative Study at Nepalgunj Medical College and Teaching Hospital - Sharma, Anshu; Saxena, Ravinder; Paudel, Dhundi Raj; Shrestha, Kumar (Journal of Nepalgunj Medical College, 2020)
Introduction: Hearing impairment is the most common congenital abnormality that occurs in 1 to 4/1000 newborns. It has a profound effect on their optimal development of language, speech and cognitive skill. Early detection in order to achieve effective treatment is essential. An association between low birth weight and hearing loss is commonly associated with multiple risk factors that can alter hearing in a synergistic fashion. Universal neonatal hearing screening programs have become widely implemented aiming for the screening, confirmation of the diagnosis and intervention by 1, 3 and 6 months respectively. Transient Evoked Otoacoustic emissions is one of the test found to be a quick, objective, non-invasive, accurate and easy test for early detection of this problem. Aims: Early detection of hearing loss in neonates focusing on low birth weight for early optimum rehabilitation. Methods: A comparative case control study conducted in 100 neonates under 2 groups. 50 neonates with low birth weight and 50 with normal birth weight who were born at NGMCTH, Kohalpur. Their hearing evaluation was done with Transient Evoked Oto Acoustic Emission (TEOAE). Results: The total referral rate was 12 % and pass rate was 88 %. The referral rate in LBW group was 20 % and 4 % in normal weight neonates. The pass rate in low birth weight was 80 % and 96 % in normal weight babies. Conclusion: Hearing impairment is a severe consequence in neonates with low birth weight. To decrease the economic and social burden of effects of hearing loss, it is assumed that newborn screening can immeasurably improve the future of newborn with early rehabilitation.